2008
DOI: 10.1007/s00431-008-0722-1
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Kawasaki disease in patients younger than 1 year of age: a possible inherent risk factor

Abstract: Kawasaki disease (KD) patients younger than 1 year of age are at especially high risk of developing coronary artery abnormalities (CAA). To define the clinical characteristics of this group, as well as the risk factors predisposing them to CAA, we reviewed the medical records of 136 KD patients younger than 1 year of age who were treated at the Korea University Medical Center from January 2001 to July 2006. Of these patients, 16 developed CAA (11.8%). The CAA(+) group had a longer duration of total fever than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 20 publications
3
14
0
3
Order By: Relevance
“…This might reflect the extra time required to rule out other diagnoses and refer a patient to specialized centers to confirm the diagnosis, especially in light of the fact that the frequency of alternate incorrect diagnosis was equivalent between groups. Difference in time to diagnosis between patients with and without incomplete KD (~1 day interval) was similar than in previous studies [20,26]. Longer interval between symptom onset and diagnosis associated with incomplete KD presentation has been previously reported [14,20,26].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This might reflect the extra time required to rule out other diagnoses and refer a patient to specialized centers to confirm the diagnosis, especially in light of the fact that the frequency of alternate incorrect diagnosis was equivalent between groups. Difference in time to diagnosis between patients with and without incomplete KD (~1 day interval) was similar than in previous studies [20,26]. Longer interval between symptom onset and diagnosis associated with incomplete KD presentation has been previously reported [14,20,26].…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have suggested that infants less than 12 months and older children are more likely to present with an incomplete clinical picture [1,6,10,17,19,20,26] and that incomplete KD is associated with longer interval between symptoms onset and treatment [14,24]. The association of incomplete presentation with coronary artery outcomes remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…The proportion of children with Table 3 Pediatr Cardiol (2012) 33:513-520 517 incomplete KD was significantly higher among children with CALs than among those without CALs (40.7 vs. 21.5%), and multivariate analysis showed that children with incomplete KD were at 3.04-fold higher risk for CALs. A higher prevalence of CALs in patients with incomplete KD also has been reported in a Japanese nationwide survey [26], and incomplete KD was significantly associated with the development of CALs in KD patients younger than 1 year [32].…”
Section: Discussionmentioning
confidence: 78%
“…These findings indicate that the association between incomplete KD and CAL may be due to delays in adequate treatment [32]. However, selection bias also is a possibility because the presence of CALs could be used as a diagnostic criterion of KD for patients with at least three of the five principal clinical features of KD.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, incomplete KD was shown to be associated with delayed diagnosis and treatment [1,8,17], and delayed treatment for KD was also reported to be a risk factor for the development of CALs [3,19,21]. Therefore, in order to prevent development of CALs in KD, it is important to recognize differences in clinical risk factors for CALs between the two types of KD and to clinically manage the high risk factors observed in incomplete KD patients.…”
Section: Introductionmentioning
confidence: 94%